Molecular evidence of Babesia species in Procyon cancrivorus (Carnivora, Procyonidae) in Uruguay - Thompson, Carolina Soledad; Mangold, Atilio Jose; Félix, María L.; Carvalho, Luis A.; Armúa-Fernández, María Teresita; Venzal, José Manuel (2018)
The crab-eating raccoon (Procyon cancrivorus) is a carnivore widely distributed from southern Central America to all South American countries except Chile. In the Southern cone of America, P. cancrivorus has been found parasitized by several Amblyomma spp. Particularly, in Uruguay, A. aureolatum is the only tick found in this wild carnivore. Piroplasmid hemoparasites were found in Procyon lotor from North America and Japan. In this work, molecular evidence Babesia sp. DNA was found in blood and tissues from road-killed P. cancrivorus from different locations in Uruguay. PCRs targeting 18S rRNA gene were carried out. Subsequently, the obtained amplicons were sequenced and full-length sequences was assembled. A phylogenetic tree was constructed and revealed that the Babesia sp. found in this work clustered with other 18sRNA sequences of Babesia spp. obtained from P. lotor from Japan and USA, along with Babesia spp. of maned wolf and I. ovatus. This is the first report of molecular evidence of Babesia sp. parasitizing P. cancrivorus.